Regulated and unregulated emissions and exhaust flow measurement of four in-use high performance motorcycles. (April 2022) - Pechout, Martin; Jindra, Petr; Hart, Jan; Vojtisek-Lom, Michal
Abstract: Exhaust emissions from four larger motorcycles, 599–1078 cm 3 engine displacement, 2008 to 2015 model years, were measured on a chassis dynamometer using cold and hot engine start World Motorcycle Transient Cycle. Raw exhaust gas was sampled and analyzed online by a portable FTIR analyzer, providing mid-infrared spectra which was resolved for greenhouse gases CO2, methane and N2 O, and for NO, NO2, NH3, CO and formaldehyde. Total number of non-volatile particles was measured by a portable counter. Particle size distributions were measured by fast electric mobility sizers, each with a different diluter. As a novel approach, useful for on-road measurements, exhaust flow was measured using a high time resolution Pitot tube, resolving rapid pulsations and reverse flows in the exhaust pipe which were often of higher magnitude than the average flow. The fuel consumption inferred from carbon emissions calculated from measured exhaust flow and the exhaust gas composition measured by the portable FTIR was, for all bikes, within 6% of the gravimetric fuel consumption measurement. The CO2, CO and NO emissions based on diluted exhaust gas sampled from a full-flow dilution tunnel were comparable to those based on raw exhaust gas composition and exhaust flow measured by the fast-response Pitot tube. Emissions of NH3 were 27–273 mg/km and were associated primarily with fuel-rich operation during transients, while emissions of NO were 30–509 mg/km were associated with slightly lean operation and/or high exhaust flows, suggesting the three-way catalytic converters were perhaps undersized, but generally working, and the emissions of NO and NH3 are attributed primarily to non-stoichiometric operation, primarily during transients. Methane and N2 O constituted about 1% of the global warming potential of CO2 . The average number of non-volatile particles per km varied from 26 to 270 billion (2.6–27 × 10 11 ). From all particles within the 5–560 nm range, 29–75% were smaller than 23 nm. Particle sizers were reporting higher concentrations of nanoparticles when connected to a heated two-stage ejector diluter compared to a rotating disc diluter. Graphical abstract: Image 1 Highlights: CO2, CH4, N2 O, NO, NO2, NH3, formaldehyde measured with portable FTIR, WMTC cycle. Exhaust flow measured with high resolution Pitot tube capable of on-road use. Total carbon emissions within 6% (avg 3%) of direct measurement of fuel flow. NO 30–509 mg/km, NH3 27–273 mg/km, high share of non-stoichiometric transients. 26–270 billion non-volatile particles/km; 29–75% of all 5–560 nm particles <23 nm.